Going Green: Unleashing the Potential of Green Product Knowledge and Influencer Marketing in Eco-Friendly Sanitary Product Selection - Agustina, Silpia; Amran, Ali; Dewi, Srie Wijaya Kesuma; Komalasari, Yunika; Putriyandari, Rofily; Drajat, Devi Yuniati (Journal of International Conference Proceedings, 2023)
This study examines the influence of green product knowledge and influencer marketing on purchase intention for eco-friendly sanitary products under the brand Nadnad. The data utilized in this research is primary data gathered by a survey method by giving questionnaires to 100 respondents residing in the city of Bandung, with respondent ages ranging from 15 to 35 years. Respondent selection was conducted by utilizing a non-probability sampling approach with purpose sampling techniques. The type of research is a descriptive and verificative survey employing multiple regression analysis. The findings of this study, green product knowledge has a partially significant and positive impact on purchase intention, and influencer marketing has a partially significant and positive impact on purchase intention as well. Furthermore, green product knowledge and influencer marketing, have simultaneously significant and positive impacts on purchase intention. This research provides a deeper understanding of the importance of green product knowledge in increasing consumer purchase intention towards eco-friendly sanitary products and can encourage companies to consider influencer marketing strategies as an effective method for promoting eco-friendly products.